ESBMC v7.3: Model Checking C++ Programs Using Clang AST - Song, Kunjian; Gadelha, Mikhail R.; Brauße, Franz; Menezes, Rafael S.; Cordeiro, Lucas C. (Anais do Simpósio Brasileiro de Métodos Formais (SBMF); 2023: Anais do XXVI Simpósio Brasileiro de Métodos Formais, 2023)
This paper introduces ESBMC v7.3, the latest Efficient SMT-Based Context-Bounded Model Checker version, which now incorporates a new Clang-based C++ front-end. While the previous CPROVER-based front-end served well for handling C++03 programs, it encountered challenges keeping up with the evolving C++ language. As new language and library features were added in each C++ version, the limitations of the old front-end became apparent, leading to difficult-to-maintain code. Consequently, modern C++ programs were challenging to verify. To overcome this obstacle, we redeveloped the front-end, opting for a more robust approach using Clang. The new front-end efficiently traverses the Abstract Syntax Tree (AST) in-memory using Clang APIs and transforms each AST node into ESBMC’s Intermediate Representation. Through extensive experimentation, our results demonstrate that ESBMC v7.3 with the new front-end significantly reduces parse and conversion errors, enabling successful verification of a wide range of C++ programs, thereby outperforming previous ESBMC versions.